Effects of exogenous calcium on flavonoid biosynthesis and accumulation in peanut roots under salt stress through multi-omics - Gao, Yan; Dong, Xuan; Wang, Rongjin; Zhang, Yongyong; Hao, Fei; Niu, Xuguang; Zhang, Hui; Lin, Guolin (Frontiers in Nutrition, 2024)
Flavonoids, endowed with potent antioxidant properties, are pivotal in bolstering plant resilience against abiotic stressors. While exogenous calcium has effectively diminished flavonoid levels in roots, the precise mechanism underlying flavonoid regulation by exogenous calcium in peanut roots amidst salt stress remains elusive. This investigation conducted a comprehensive profiling of metabolites in peanut roots through a widely targeted metabolome and an absolute quantitative metabolome of flavonoids. The findings unveiled a dynamic shift in flavonoid composition, wherein salt stress prompted peanut roots to produce an array of metabolites and flavonoids, consequently enhancing the activities of key enzymes in the flavonoid biosynthesis pathway and augmenting the accumulation of monomeric flavonoids. Conversely, exogenous calcium exerted an opposing influence. This study offers novel insights into flavonoids' physiological and ecological roles in mitigating diverse environmental stressors within a commercially significant crop.Flavonoids possess antioxidant properties and are crucial in enhancing plant resistance to abiotic stress. Exogenous calcium has been found to regulate the biosynthesis and accumulation of secondary metabolites, including flavonoids. However, the mechanism by which exogenous calcium influences flavonoid regulation in peanut roots under salt stress remains unclear. In this study, four treatment conditions were established: no salt stress, salt stress, exogenous calcium, and a combination of salt stress and exogenous calcium. The peanut root flavonoid profile was comprehensively analyzed using both a broadly targeted metabolomic approach and an absolute quantitative flavonoid metabolome. A total of 168 flavonoids were identified in the broad-target metabolome, while 68 were quantified in the absolute quantification analysis. The findings revealed that salt stress generally increased flavonoid content in peanut roots, while co-treatment with exogenous calcium significantly reduced this accumulation. Additionally, the activities of key enzymes and the expression of genes involved in the flavonoid biosynthesis pathway were upregulated under salt stress, but downregulated following the combined treatment. This study offers valuable insights into the physiological and ecological roles of flavonoids in response to environmental stressors in economically important crops.